Enhancing Organizational Performance Through Strategic Technology Alliances: A Study on Malaysian Manufacturers - Jabar, Juhaini; Othman, Norfaridatul Akmaliah; Idris, Mohd Asmadi (International Association of Computer Science and Information Technology Press (IACSIT), 2011)
Organizations are constantly searching for strategic methods in order to stay competitive. This paper examines the relationship between organizations’ resource availability and absorptive capacity as well as type of alliances with organizational performance. A total of 2,500 Malaysian manufacturers were surveyed resulting in 335 of usable responses were then analyzed using Structural Equation Modeling (SEM). The result establishes that Malaysian manufacturers need to increase their efforts in increasing internal resources that are the source of competitive advantage in order to achieve superior manufacturing performance.